Body composition, energy, and fluid turnover in a five-day multistage ultratriathlon: A case study - Knechtle, B.; Knechtle, P.; Andonie, J. L.; Kohler, G. (Research in Sports Medicine, 2009)
A multistage ultraendurance triathlon over five times the Ironman distance within five consecutive days leads in one ultraendurance triathlete to minimal changes in body mass (BM; -0.3 kg), fat mass (FM; -1.9 kg), skeletal muscle mass (SM; no change), and total body water (TBW; +1.5 l). This might be explained by the continuously slower race times throughout the race every day and the positive energy balance (8,095 kcal), although he suffered an average energy deficit of -1,848 kcal per Ironman distance. The increase of TBW might be explained by the increase of plasma volume (PV) in the first 3 days. The increase of PV and TBW could be a result of an increase of sodium, which was increased after every stage. We presume that this could be the result of an increased activity of aldosterone.